4. Oblicz:

a) (-6)-(-8)=
7-(-3) =
(-14)-6=
9-12 =

b) (-3) -10 =
(-11)-(-9) =
(-8)-(-7)=
(-9) -2 =

c) 13-(-13) =
(-40) - (-40) =
(-22)-40 =
(-53)-30 =

d) (-60)-(-30) =
(-180) - 20 =
710- (-10) =
(-150)-(-200) =​


Odpowiedź :

a) (-6)-(-8)= 2

7-(-3) = 10

(-14)-6= -20

9-12 = -3

b) (-3)-10 = -13

(-11)-(-9) = -2

(-8)-(-7)= -1

(-9)-2 = -11

c) 13-(-13) = 26

(-40) - (-40) = 0

(-22)-40 = -62

(-53)-30 = -83

d) (-60)-(-30) = -30

(-180) - 20 = -200

710- (-10) = 720

(-150)-(-200) =50

Pozdrawiam serdecznie

A)
-14
10
20
3

B)
-13
-3
-1
-11

C)
26
80
-62
-83

D)
-30
-200
720
50
Mam nadzieje że dobrze